Dual-bactericidal wood-reinforced hydrogel sensor for healthcare monitoring and information transmission - Hengyao Zhou; Hongwei Zhang; Yaobo Wang; Fanjun Yu; Yanjun Xie; Tianpeng Zhang; Zefang Xiao (Chemical Engineering Journal, 2026)

Ammonia-hydrogen combination engine with injecting jet ignition (IJI): the concepts and ignition mechanism - Fanjun Guo; Jin Yu; Shiyong Liao; Yituan He (Fuel, 2025)

Emulsion coating: One-pot method preparing the sealable microporous surfaces with antibacterial and antithrombotic properties - Jingze Liu; Yueze Hong; Yao Xiong; Yage Hu; Jiaqi Wang; Yuan Wei; Tong Wang; Haichao Yu; Ruipeng Xue; Li Yang; Gaocan Li; Rifang Luo; et al. (Chemical Engineering Journal, 2025)

Tunicate cellulose nanocrystal reinforced conductive multi-responsive hydrogel with super flexible, fatigue resistant and self-healable capability for antibacterial flexible sensors - Qin Yang; Mingtao He; Zhongrui Yu; Yijie Liu; Yilan Bai; Tianci Liu; Tingting Wang; Lingtao Meng; Fanjun Meng; Qinglin Ma; Yuju Che (Chemical Engineering Journal, 2024)

Modification with lignin-based N-P flame retardant to improve the flame retardancy and smoke suppression of wood - Fanjun Yu; Zhichen Ba; Zhizun Gao; Yonggui Wang; Yanjun Xie; Haigang Wang; Zhe Qiu; Zefang Xiao (Chemical Engineering Journal, 2024)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Ultrafast Self-propelling directionally water transporting wood via cell wall reshaping for water manipulation - Zhe Qiu; Fanjun Yu; Dan Xu; Zengbin Wang; Junya Huang; Shuo Wang; Yanxiao Yang; Yonggui Wang; Jian Li; Zefang Xiao; Yanjun Xie; Kai Zhang (Chemical Engineering Journal, 2023)

Sensory–sympathetic coupling in superior cervical ganglia after myocardial ischemic injury facilitates sympathoexcitatory action via P2X7 receptor - Jun Liu; Guilin Li; Haiying Peng; Guihua Tu; Fanjun Kong; Shuangmei Liu; Yun Gao; Hong Xu; Shuyi Qiu; Bo Fan; Qicheng Zhu; Shicheng Yu; et al. (Purinergic Signalling, 2013)